Enhancing environmental monitoring: utilizing plant and soil assays to track pollution in a Turkish organized industrial zone - ÖZYİĞİT, İBRAHİM İLKER (My University, 2023)
The aim of the current investigation was to determine the concentration of different metals in Mentha spicata L. subsp. tomentosa plants and soils in order to highlight the pollution level in a Turkish Organized Industrial Zone in Dilovasi District, in Kocaeli City. The concentration of metals in plant and soil samples were examined. When the soil values were examined, the highest cadmium, chromium, copper, iron, nickel, and lead levels were collected from the location which is hosting numerous industrial facilities. All elements except boron and copper, exceeded normal limits in the leaf samples while cadmium, chromium, iron, nickel, lead, and zinc reached \"toxic levels\" in leaf samples. Heavy metals were accumulated in leaves more than rhizomes. Mineral element uptake and accumulation were affected from heavy metal amounts, especially in rhizomes. Although washing procedure notably reduced the concentration of some heavy metals in leaves samples, the reduced values were higher than acceptable levels in some locations of the district. According to the data, it may be said that the region, especially its industrialized parts are heavily polluted by heavy metals. Moreover, in the accordance with the fact that, the highest values of elements were determined in regions having considerable industrial activity such as metal and plastic processing facilities. Additionally, Mentha spicata plants exhibited higher heavy metal values in areas with high heavy metal content in the soil, and lower heavy metal values in areas with low heavy metal concentration. These findings indicate that Mentha spicata, a plant known for its medicinal and culinary uses, can be considered as an effective biomonitor for heavy metal pollution in the region. Consequently, constant inspection is required to prevent the excessive buildup of metals in the region and similar areas with comparable characteristics in terms of human life.
Keywords: Fizik; Atom ve Molekül Fiziği; Kimya; Analitik Kimya; Fizikokimya; Spektroskopi; Temel Bilimler; Physics; Atomic and Molecular Physics; Chemistry; Analytical Chemistry; Physical Chemistry; Spectroscopy; Natural Sciences; Temel Bilimler (SCI); KİMYA, ANALİTİK; SPEKTROSKOPİ; FİZİK, ATOMİK, MOLEKÜLER VE KİMYASAL; Natural Sciences (SCI); CHEMISTRY; PHYSICS; CHEMISTRY, ANALYTICAL; SPECTROSCOPY; PHYSICS, ATOMIC, MOLECULAR & CHEMICAL; Fizik Bilimleri; Atom ve Moleküler Fizik ve Optik; Physical Sciences; Atomic and Molecular Physics, and Optics; Bioaccumulation; Dilovasi district; elements; Mentha spicata